Knausenstein's monster. portraits of the author in a post-anthropocentric mirror. Issue 1 (2nd January 2021) - Haarder, Jon Helt
ABSTRACT: This article introduces the term 'performative biographism' and sees the recent boom in autofictional writing as part of this trend. With Karl Ove Knausgård's My Struggle as my example, I relate performative biographism to the turn to things in recent theory in order to bring out two aspects of a post-anthropocentric conception of authorship. It turns out that this has relevance for literature's modes of existence in general.